PREVALENCE AND ASSOCIATED FACTORS OF ORAL NON-CANDIDA ALBICANS CANDIDA CARRIAGE IN DENTURE WEARERS IN SANA'A CITY- YEMEN - Abdulsalam Al-Haddad, Khaled; Al-dossary, Omar Ahmed Esma’il; A. Al-Shamahy, Hassan (Universal Journal of Pharmaceutical Research, 2018)
Objective: The objective of this study was to contrast the prevalence and species of colonization of Non-Candida albicans (NCAC) in the oral cavity of denture wearers and non-denture wearers; also asses associated risk factors of their colonization. Methods: A total of 208 subjects were studied: 104 denture wearers and 104 non-denture wearers, matched by age, sex, comprised the experimental control groups, respectively. Each subject was instructed to perform oral rinsing using a phosphate-buffered saline solution, which was expectorated processed for the recovery of Candida species on on Sabouraud dextrose agar. Isolates were identified by culturing on chromogenic Candida agar noting species-specific colony characteristics. Results: There was a significant oral carriage rate of NCAC among denture wearers (5.83% versus 11.1% in controls) with associated risk factor (5.4) (PV<0.001). The most common isolated NCAC were C. Krusi C. tropicalis with significant OR (5.5 4.7 respectively). When co-infections were considered, there was highly significant association of C. albicans + C. krusi oral colonization in cases (OR=4.56, PV<0.001). There was a significant oral carriage rate of NCAC among male denture wearers (36.9%, OR=6.6, PV˂0.001). In addition, there was a significant rate of NCAC colonization with complete denture (rate= 50%, OR=2.4, PV= 0.02). While no significant increase associated with colonization of NCAC with partial, acrylic /or chrome cobalt denture. Conclusion: Based on the results of this study ability of NCAC were greater in denture wearers than non-denture wearers, also greater risk of NCAC were found with males, older ages, complete denture. Peer Review History: Received 4 June 2018; Revised 9 July; Accepted 23 September; Available online 15 September 2018 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Mohammed Sadeg Abdullah Al-Awar, Physiology & Histopathology Queen Arwa University and Amran University, Yemen, momed.sadeg@gmail.com Dr. Mahmoud S. Abdallah , University of Sadat city, Egypt, dr_samy777@yahoo.com